High time - Rothschild, Hannah, 1962- (House of Trelawney, 2023)
"A modern English comedy of morals and manners, about a highborn family of outrageous characters, in a story that proves revenge can be sweet. In the months leading up to the Brexit referendum, Ayesha, the beautiful, young secret daughter of the late Enyon Trelawney, has married the much older thuggish banker Tomlinson Sleet with whom she has a young daughter, Stella. Ayesha is busy restoring the once run-down Trelawney Castle in Cornwall, which Sleet has bought, to its former glory, as well as studying art at the Courtauld in London. The elderly Countess Clarissa-still ensconced on the property--the host of a camp television show, is about to head into a disastrous marriage. Lady Jane has separated from the hopeless Trelawney heir Kitto, who is crazier than ever, and found an enlightened woman to keep her company abroad. Sleet is becoming increasingly difficult, distracted by the seductive and ruthless bitcoin goddess Zamora, but Kitto's sister Blaze and her husband, Joshua, will support Ayesha's clever plan as she discovers shocking secrets, takes action, and brings the family together."--